Inspection model development for production machines based on downtime record - Nur Hazirah, Sa'ari
In the production line, the main objective of the machines to provide the good quality of products at the time given and follow the customer requirement to accomplish customer’s satisfaction. To reach the objective, the production line should running in smooth flow without or less breakdown. Nevertheless, the real production with the ineffective maintenance strategy becomes barrier to the production to achieving the objective. Reasonably, this problem contributes to high production lost, production defect due to reject product (if the breakdown occurs during the machine is operating) and increasing the maintenance cost. Inspection is one of the Preventive Maintenance (PM) strategies that can be used to reduce machines breakdown problem in the production line. Conversely, the application of inspection in term of how many times of the inspection should be done at the unit of time (such as per month) is the main issue. To answer this question, an adequate maintenance analysis based on inspection must be accomplished. Most of the existing study is focus to inspection of single machine at the state of constant failure rate. There is no consideration for machine in the state of decreasing and increasing failure rate. Hence, the inspection strategy introduce to the machine at decreasing failure rate state to give extra value to the production machines by reducing machines breakdown due to continuous monitoring the machine condition and do correction or maintenance if needed. In this research, an inspection model of maintenance analysis by considering the failure time of the machines is developed in order to determine the optimal inspection frequency of the critical machines in the production line. In addition, the inspection strategy that used can maximize the output of production machines in term of product and service. In order to confirm this model, a case study was carried out on the automotive industry in Malaysia. The result from failure analysis have identified that all the critical machines in the state of decreasing failure rate and the failure characteristic information was used for the next analysis. Result shows that the machine follows the Weibull distribution and for inspection modeling also used the Weibull function to identify the inspection frequency for the critical machines. Therefore, the result shows that have relationship between two inspection model base on profit and downtime.